Fibromyalgia comorbidity in Systemic Lupus Erythematosus patients: assessing impact on quality of life - Jade A. M. Monteiro; Alexia L. H. Gama; Joao C. S. Oliveira; Matheus V. Falcao; Ana Karla G. Melo; Danielle C. S. Egypto; Alessandra S. Braz (Advances in Rheumatology)
Abstract Introduction The prevalence of Fibromyalgia in patients with Systemic Lupus Erythematosus (SLE) is significantly higher compared to the general population. Despite this frequent association, Fibromyalgia remains underdiagnosed and consequently inadequately treated, negatively affecting the quality of life of these patients. Objective This study aims to evaluate the occurrence of Fibromyalgia and its impact on the quality of life of Brazilian patients with SLE treated at a University Hospital in the state of Paraiba. Materials and methods This descriptive, observational, and cross-sectional study included patients with SLE diagnosed according to the 2012 criteria of the Systemic Lupus Erythematosus International Collaborating Clinics (SLICC). The occurrence of Fibromyalgia was assessed using the American College of Rheumatology (ACR) criteria of 1990 and 2010/2011, revised in 2016. Quality of life was evaluated using the Short-Form 36 (SF-36) questionnaire for all patients, while the Fibromyalgia Impact Questionnaire (FIQ) was applied to those diagnosed with Fibromyalgia. Results The sample comprised 107 SLE patients, with an average age of 54.1 years (SD:12.1), of whom 95.4% (102) were women. The prevalence of Fibromyalgia among SLE patients was 19.1% (21), all of whom were women with a mean age of 45.6 years (SD 9.6). The SF-36 scores of SLE patients with Fibromyalgia were consistently lower across all eight domains compared to those without Fibromyalgia, indicating a significant negative impact of this comorbidity. Conclusion: These findings are consistent with existing literature, highlighting the significant negative impact of Fibromyalgia on the quality of life of patients with SLE. Conclusion These findings are consistent with existing literature, highlighting the significant negative impact of Fibromyalgia on the quality of life of patients with SLE.